2019
DOI: 10.1007/s00221-019-05487-1
|View full text |Cite
|
Sign up to set email alerts
|

Single finger movements in the aging hand: changes in finger independence, muscle activation patterns and tendon displacement in older adults

Abstract: With aging, hand mobility and manual dexterity decline, even under healthy circumstances. To assess how aging affects finger movement control, we compared elderly and young subjects with respect to (1) finger movement independence, (2) neural control of extrinsic finger muscles and (3) finger tendon displacements during single finger flexion. In twelve healthy older (age 68-84) and nine young (age 22-29) subjects, finger kinematics were measured to assess finger movement enslaving and the range of independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 71 publications
1
13
0
Order By: Relevance
“…Interestingly, the reduced cortical distance between index and middle finger representations in older adults may explain the increased motor enslaving of the middle finger during index finger flexion, and the lower range of independent movements specifically of the index finger in older adults ( Van Beek et al, 2019 ). This can be assumed because passive stimulation of the fingers also activates finger maps in the primary motor cortex (see Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the reduced cortical distance between index and middle finger representations in older adults may explain the increased motor enslaving of the middle finger during index finger flexion, and the lower range of independent movements specifically of the index finger in older adults ( Van Beek et al, 2019 ). This can be assumed because passive stimulation of the fingers also activates finger maps in the primary motor cortex (see Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings highlight the importance of combining laboratory measures of perceptual precision with complex everyday task assessments that detail the relevance of fine-grained topographic map changes for everyday hand use. Interestingly, the reduced cortical distance between index and middle finger representations in older adults explains the increased enslaving of the middle finger during index finger flexion in older adults (Van Beek et al, 2019), and may relate to use-dependent plasticity (Makin et al, 2013a). During everyday hand movements, the index and the middle finger correlate less with each other than other neighbouring fingers (Belić and Faisal, 2015), and the index finger is the most independent of the four fingers (Ingram et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the reduced cortical distance between index and middle finger representations in older adults may explain the increased motor enslaving of the middle finger during index finger flexion, and the lower range of independent movement specifically of the index finger in older adults (Van Beek et al, 2019). This can be assumed because passive stimulation of the fingers also activates finger maps in the primary motor cortex (see Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, reports on age-related changes in enslaving are ambiguous and seem to be task specific. A number of studies reported lower enslaving in the healthy older adults (Kapur et al, 2010b;Oliveira et al, 2008;Shinohara et al, 2003aShinohara et al, , 2003bShinohara et al, , 2004Yu et al, 2010), while other studies reported higher enslaving (Mirakhorlo et al, 2018;van Beek et al, 2017van Beek et al, , 2019.…”
Section: Enslaving In Cases Of Impaired Finger Force Controlmentioning
confidence: 99%